ملامح الافتراض المسبق في الحديث القدسي بالمنظور اللساني الحديث- النظرية السياقية انموذجا- - حويذق, محمد العربي; تكتك, اكرام (جامعة الوادي - University of Eloued, 2021)
ملخص: يمثّل الافتراض المسبق أهم درجات الدّرس التّداولي الحديث؛ اذ يسعى إلى فهم معاني النّصوص وفكّ شفراتها, وإذكاء شُعلة الدّلالة التّداولية المخفيّة وراء الدّلالة الحرفيّة, مجانباً التّصريح إلى التّلميح, مراهناً على خبرة المخاطَب وقدرته في اكتشاف تلك المعاني, وحريصاً على سرعة فهمه للدّلالات الضمنيّة والذي ينطوي ورائها قصد المتكلّم.. ويندرج الخطاب الدّيني المتمثّل في الحديث القدسي ضمن هذه النّصوص والّتي يسعى الافتراض المسبق إلى سبر أغوارها واقتناص قصد المخاطِب ضمن السّياقات المتعدّدة فيما يأمله من المخاطَب وتوجيه ذهنه في ذلك تأتي النّظرية السّياقيّة لتجيب على هذه الأسئلة : ما السّياق و ما هو موضوعه؟ وفيما تكمن الأهميّة التّخاطبيّة للدّلالة السّياقيّة في الحديث القدسي ؟ Abstract Presumption represents the most important step of the modern deliberative lesson; As it seeks to understand the meanings of texts and decipher their codes, and to stoke the flame of the deliberative sign hidden behind the literal connotation, avoiding the statement to allusion, betting on the addressee's experience and his ability to discover those meanings, and keen on his speed of understanding the implicit connotations which is behind the intention of the speaker. The religious discourse represented by the Qudsi Hadith is included in these texts, which the presumption seeks to explore and capture the intention of the addressee within the various contexts with what he hopes of the addressee and directs his mind in that. Contextual theory comes to answer these questions: What is the context and what is its object? And what is the communicative importance of the contextual connotation in the Hadith Qudsi?
مقال
Keywords: الافتراض المسبق ; presumption ; السياق ; context ; الدلالة السياقية ; contextual connotation ; الحديث القدسي ; divine Hadith